Anthropology and ethnobotany in health mediation: an illustration of a clinical, personalized approach for Haitian migrants in a French Guianese hospital - Tareau, Marc-Alexandre; Demars, Yoris; Alcouffe, Leslie; Pierre-Louis, Ruth; Walter, Gaelle; Djossou, Félix; Vignier, Nicolas; About, Frédégonde (Frontiers in Public Health, 2024)
Introduction In French Guiana, a European territory in Guiana shield in the Amazon area, close to 40% of the current population was born abroad. In this context, it is important to listen to the experiences of migrants to better understand the difficulties encountered within the healthcare pathways. This is the aim of ANRS Parcours d’Haïti project, an epidemiological, biographical and socio-anthropological study conducted on a representative sample of the Haitian community in French Guiana and focusing on the social determinants of health. Methodology Within the framework of this study, the Infectious and Tropical Diseases clinical team of Cayenne Hospital has established close collaboration with health mediators and the ethnobotanist anthropologist of the study. To illustrate the contribution of a personalized approach to health mediation, we report the case of a migrant woman of Haitian origin admitted to the Infectious and Tropical Diseases Unit. We highlight the different socio-cultural aspects addressed and their place in the care process through a thematic discussion and socio-anthropological analysis of the care relationship, based on participatory ethnography and inductive analysis of an in-depth interview with the patient. Result This example illustrates the need for a multidisciplinary approach to ensure culturally adapted care for patients. Personal interviews are important because they allow to better take into account the cultural specificities of patients’ experiences and the socio-cultural environment in which they live (and especially, in the case of Haitian patients, their religious affiliation). By allowing them to speak and express themselves freely, they integrate not only their own cultural baggage, but also their own expectations and representations of the disease they suffer from and how it should be treated. Ultimately, this tripartite collaboration between patient, caregiver, and anthropologist or health mediator leads to a better therapeutic alliance. Conclusion The analysis of this health care relationship is emblematic of the issue of cultural competence and pre-conceptualizes what intercultural mediation in health care could be, as close as possible to the caregiver and the individual.